PENANAMAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR: Sebuah Tinjauan di SD Kedungpring, Pleret, Bantul - Nisfi Anisah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
Character education is an important thing that must be provided early on to students. The rapid development of the millennial era has affected changes and developments in children. This also affects the character of the child. Schools as educational institutions have the task of instilling character education in children. The aims of this study were (1) to find out the implementation of character education in SD Kedungpring, (2) to find out the character values ​​instilled in SD Kedungpring. This research is a qualitative research with a phenomenological approach conducted at Kedungpring Elementary School. This study used a purposive sampling type, where this study took research subjects including teachers, school principals, and students at Kedungping Elementary School. The methods used to collect data include observation, interviews, questionnaires and documentation. The results of this study indicate that Kedungpring Elementary School has implemented character education for students through a multi-approach that includes a micro (individual) approach, a meso approach and a macro approach. These three approaches are then applied by integrating in all subjects, developing the culture of the educational unit, carrying out extracurricular activities, and getting used to behavior in life. The character values ​​instilled in Kedungpring Elementary School include religious values, honesty, responsibility, discipline, respect, and care for the environment. The process of planting character education involves the role of parents and the surrounding community.